Thermodynamical analysis of bioconvective chemically reactive and magnetized thermal-radiative bidirectional Casson nanofluid flow with heat-sink-source aspects - Khan, Waqar Azeem; Hussain, Zubair; Ali, Mehboob; Ahmad, Wakeel; Almutairi, Shahah (Journal of radiation research and applied sciences, 2024)
The determination of the present investigation is to interpret the constitution of MHD steady three-dimensional Casson nanofluid flow containing gyrotactic microorganism over a stretching sheet. Besides, the possessions of thermophoresis, thermal radiation and Brownian motion are considered in this investigation. We convert the subsequent non-linear PDE's are into ODE's by using suitable similarity variables. We numerically evaluate the obtained non-linear ordinary differential equations by using Bvp4c technique in mathematical solver MATLAB. The Casson fluid parameter related directly with the growing enactment of the temperature portrait. It can be detected that the concentration profile amplifies for the rising estimations of Porosity and magnetic parameter. The opposite behavior is observed in the microorganism field with growing estimates of the bioconvection Lewis number.